Venomous animals in Pernambuco: children at risk - Maria Carlinda Arôxa de Albuquerque; Cesar Romero do N Lyra Filho; Maria Lucineide Porto Amorim; Iasmim Bezerra Lopes Lins; Paulo Victor Cruz de Lima; Maria Júlia Gonçalves de Mello (Instituto Materno Infantil de Pernambuco, 2022)
Abstract Objectives: to analyze the epidemiological and clinical aspects of accidents caused by venomous animals in children under 15 years old. Methods: a cross-sectional study with an analytical component using secondary data from Centro de Informação e Assistência Toxicológica de Pernambuco (CIATox-PE), (Poison Center in Pernambuco)), in 2017 to 2019. Notifications of accidents caused were included in the studied age group and evaluated the characteristics of poisoning (animal classification, exposure zone, place and time of the occurrence and specific use of serum therapy), and of the patient (sociodemographic variables, clinical condition and evolution). The analysis performed in STATA® 13.1 presents frequency distribution tables and Pearson's chi-square for comparison. Results: of the 2678 notifications, 82,8% were scorpionism and 10, 8% snakebite. The age group of1 to 9 years old (70.5%) and being male (54.1%) were predominant. Most of the cases occurred in urban area (80.9%), in Recife (67.3%), inside the victim's residence (83.9%) and at night (47.3%). The majority (87.1%) were classified as 'mild severity', 10% received antivenom therapy and one died (by scorpionism). Two cases of snakebite in the workplace were registered. Conclusion: there was a high frequency of accidents caused in the urban area, which may be related to the lack of urban planning and sanitary education. The accidents caused among children in the household environment and the suspicion of child labor in the age group of 10 to 14 years old were also highlighted which favors the development and habits of the venomous animal.